Can strong substorm-associated MeV electron injections be an important cause of large radiation belt enhancements? - Kim, Hee-Jeong; Noh, S. J.; Lee, D. Y.; Lyons, L.; Bortnik, J.; Nagai, T.; Choe, W.; Hua, M. (Frontiers in Astronomy and Space Sciences, 2023)
It has become well-established that strong outer radiation belt enhancements are due to wave-driven electron energization by whistler-mode chorus waves. However, in this study, we examine strong MeV electron injections on 10 July 2019 and find substantial evidence that such injections may be a crucial contributor to outer-radiation belt enhancement events. For such an examination, it is essential to precisely separate purely temporal flux changes from spatial variations observed as Van Allen Probes move along their orbits. Employing a novel “hourly snapshot” analysis approach, we discover unprecedented details of electron flux evolutions that suggest that for this event, the outer belt enhancement was not continuous but instead intermittent, mostly composed of 4 large discrete injection-driven flux increases. The injections appear as sharp flux increases when observed near apogee. Otherwise, by comparing hourly snapshots for different times, we infer injections and infer temporally stable fluxes between injections, despite strong and continuous chorus emission. The fast and intermittent electron flux growth successively extending earthwards implies cumulative outer belt enhancement via a series of repetitive inward transport associated with injection-induced electric fields.